Underhand Land Buying and Selling Practices and Their Legal Consequences - Putry, Dian (Jurnal Konstatering, 2024)
Underhanded land transactions, which are carried out informally without a legal process regulated by the government, are still common in various regions including Gondai Village. Although practical, these transactions carry significant legal risks. This study uses Lawrence M. Friedman's legal system theory, which divides the legal system into three components: structure, substance, and legal culture, to examine weaknesses in the legal system related to these transactions. This study aims to identify weaknesses in the legal system based on Friedman's theory and to develop steps to increase public legal awareness regarding land transactions. Using a qualitative approach and descriptive analysis method, data were collected through literature studies, in-depth interviews, and field observations. Underhanded land transactions show weaknesses in the structure, substance, and legal culture. To overcome this, comprehensive improvements are needed: strengthening government institutions, simplifying regulations, and improving legal culture through education and socialization. High legal awareness helps parties involved understand their rights, obligations, and risks, including aspects of the legality of land ownership, administrative requirements, and tax payments.